MODERN INNOVATIVE STORAGE TECHNOLOGIES FOR PROCESSED FRUIT AND VEGETABLE PRODUCTS (REVIEW) - S. V. Glazkov; S. V. Koptsev; N. A. Lesnikova; V. V. Bogdanova; T. K. Volodarskaya (Овощи России, 2018)
The article analyzes modern technologies for storing fruit and vegetable products and presents possible options for their modernization. From this perspective, the improvement of canning technology using non-traditional methods of processing plant raw materials is an urgent task, the solution of which will allow preserving fruit and vegetable products, reduce the amount of waste and reduce the impact of vegetable processing plants on natural water bodies. Fruits and vegetables are perishable products and require special storage conditions from the moment they are available for sale to purchase by consumers. Keeping them fresh for as long as possible is quite a challenge, as some plants are able to continue maturing even after packaging and produce ethylene, which initiates certain changes in texture and color, tissue degradation. The authors pay special attention to the aspects of innovative technologies in the creation of edible films and coatings, which are currently the only type of biodegradable polymer packaging that does not require individual collection and special conditions of disposal. This is their main difference from traditional biodegradable plastics, which were originally proposed as an alternative to synthetic polymeric materials, and all were convinced that their creation once and for all will solve the problem of waste polymer packaging, which today threatens to become a global environmental disaster. At the same time, they are always more expensive than conventional plastics, in many cases can not be subjected to joint recycling; being in the deep layers of the landfill, they emit greenhouse gas methane. In addition, the raw materials for biodegradable plastics are provided by the same soil and water resources on which food is grown today (except for a very small amount of plastics produced from agricultural waste), and therefore their raw material base will always be limited. Recommendations are formulated on the organization of effective conservation of plant raw materials, intended for further processing or sale in retail and wholesale trade networks.